SCIENTIFIC AND LEGAL OPINION ON THE ISSUES OF RESPONSIBILITY OF JUDGES IN THE CONTEXT OF COMPLIANCE OF CONSTITUTION OF UKRAINE WITH PROVISIONS OF CLAUSE 6 OF PART ONE, CLAUSES 2, 13 OF PART TWO, PART THREE OF ARTICLE 3 OF THE LAW OF UKRAINE “ON - Погорецький, М.А; Марцеляк, О.В; Прилуцький, С.В (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2015)
The scientific and legal opinion analyzes three key concepts - lustration, political and constitutional and legal liability - and determines their interrelation. It is shown that the Law on Lustration introduces a mixed institution of constitutional and political liability with the aim of cleansing state institutions, but does not create new criminal offenses. The author analyzes the compatibility of its provisions with the principle of irreversibility of the law in time and individual responsibility, as well as with the constitutional guarantees of judicial independence. The author concludes that lustration bans are not a type of disciplinary sanction, and dismissal of judges under this procedure requires a separate constitutional regulation and harmonization with the procedure enshrined in Article 126 of the Constitution of Ukraine.

У науково-правовому висновку розглянуто три ключові поняття – люстрацію, політичну та конституційно-правову відповідальність – і визначено їхній взаємозв’язок. Показано, що Закон «Про очищення влади» запроваджує змішаний інститут конституційно-політичної відповідальності з метою очищення державних інститутів, але не створює нових кримінальних правопорушень. Проаналізовано сумісність його норм із принципом незворотності дії закону в часі та індивідуальної відповідальності, а також з конституційними гарантіями незалежності суддів. Висловлено висновок, що люстраційні заборони не є видом дисциплінарного стягнення, а звільнення суддів у цій процедурі вимагає окремого конституційного врегулювання та узгодження з процедурою, закріпленою у ст. 126 Конституції України.
НАУКОВО-ПРАВОВИЙ ВИСНОВОК ЩОДО ПИТАНЬ ВІДПОВІДАЛЬНОСТІ СУДДІВ У КОНТЕКСТІ ВІДПОВІДНОСТІ КОНСТИТУЦІЇ УКРАЇНИ ПОЛОЖЕНЬ ПУНКТУ 6 ЧАСТИНИ ПЕРШОЇ, ПУНКТІВ 2, 13 ЧАСТИНИ ДРУГОЇ, ЧАСТИНИ ТРЕТЬОЇ СТАТТІ 3 ЗАКОНУ УКРАЇНИ «ПРО ОЧИЩЕННЯ ВЛАДИ» ВІД 16 ВЕРЕ